EFEKTIVITAS IMC DALAM MEMBANGUN PROMOSI BERBASIS KOMUNITAS PADA EKOSISTEM MUSIK SURABAYA : The Effectiveness of IMC in Building Community-Based Promotion in the Surabaya Music Ecosystem - Kezia Enginia Mutiara Hasian Sagala; Shienny Megawati (Universitas Trisakti, 2026)
The Effectiveness of IMC in Building Community-Based Promotion in the Surabaya Music Ecosystem. Community-based music promotion in Surabaya remains sporadic, fragmented, and difficult to measure in terms of effectiveness. This condition results in inconsistent messaging across channels and weak long-term audience engagement. It highlights the need to apply an Integrated Marketing Communication (IMC) approach to establish a more structured and sustainable promotional ecosystem. This study aims to answer the question: how effective are IMC channels in driving exposure, engagement, and attendance conversion within Surabaya’s community-based music ecosystem? The research seeks to map the specific roles of owned, earned, and paid media in guiding audiences from awareness to conversion, and to formulate contextual operational recommendations for local music ecosystem stakeholders. A qualitative method was employed through in-depth interviews with key actors in Surabaya’s music communities and independent musicians, supported by thematic coding analysis and triangulation. The findings indicate that owned media, particularly Instagram, serves as the central communication hub; earned media enhances reach and legitimacy; while paid media effectively stimulates audience decisions when organic growth slows down. The main challenges lie in irregular content publication and the overemphasis on raw reach instead of meaningful audience interaction. IMC proves to be effective when narrative consistency, channel orchestration, posting rhythm, and public documentation are aligned as one integrated communication system. Transforming promotion from incidental activities into a collectively auditable information infrastructure enhances connectivity, optimizes resources, and strengthens the sustainability of Surabaya’s creative economy.